Den prøvede familie: Det sentimentale og det antisentimentale i fiktioner om Den haitianske revolution - Ross Kjærgård, Jonas (K&K - Kultur og Klasse, 2021)
The troubled family, this article claims, is a recurring topos in the fictions of the Haitian Revolution. Most often, this topos is distinctively sentimental, designed to affect readers emotionally, and authors use the family in trouble as an emotionally charged political microcosm capable of negotiating the limits and rules of social inclusion and exclusion. In this article, Olympe de Gouges’ play L’esclavage des noirs (1792), published just months after news of the Haitian revolution reached France, is read alongside Émeric Bergeud’s Stella (1859), often heralded as the first Haitian novel. While Gouges’ play exemplifies the sentimentalism that characterized much French abolitionist thought (Festa, Dobie), the analysis also emphasizes the inegalitarian subject-object relation between the empathetic Frenchmen and the enslaved colonial workers. Writing from the Caribbean, Bergeaud deselects the standard tropes and stylistic elements favored by Gouges and other sentimental European abolitionists. In his attempt to write a foundational national novel, however, he too invokes the topos of the troubled family.